COMBINED EFFECTS OF UBIQUITOUS XENOBIOTICS OF WATER ENVIRONMENT ON THE IMMUNE SYSTEM OF THE BODY - Винарська, О. І.; Франчук, Ю. О.; Григоренко, Л. Є. (Science-based technologies, 2009)
In accordance with results of researches on the combined peroral exposure of sodium nitrate, sodium nitrite and chloroform at the levels of 1, 5 and 10 of the limited permissible concentrations (LPC) for the organism immune system it was established that immunotoxic effects of studied xenobiotics have been manifested as the development of sensitization, autosensitization, injuries in the cellular and humoral immunity links, nonspecific factors of organism defence. The effects expressiveness depended on the dose, exposure duration and combinations composition. The immunotoxic effects in the animals under combined exposure of sodium nitrite, sodium nitrate and chloroform were more expressed than in the rats exposed only by nitrite-nitrate loading in the identifical doses.